2008
DOI: 10.1007/s11605-007-0389-3
|View full text |Cite
|
Sign up to set email alerts
|

Radical Surgical Resection for Carcinoid Tumors of the Ampulla

Abstract: Ampullary carcinoid tumors are extremely rare. The present study describes the clinicopathological features and outcomes for 10 ampullary carcinoid patients who underwent radical resection from 1998 to 2005. During this study period, 294 patients underwent pancreatoduodenectomy for ampullary neoplasms in our institution. The mean patient age was 58.0 +/- 13.4 years, and seven were male. Initial clinical manifestations were jaundice in four patients, nonspecific gastrointestinal symptoms in five, and completely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 13 publications
0
24
2
1
Order By: Relevance
“…For definite diagnosis, immunohistochemical staining is needed after tumor biopsy. Because of the finding of a submucosal tumor at the ampulla on endoscopy, the rate of preoperative histological diagnosis on endoscopic biopsy is low, ranging from 14 to 66% [2, 5, 13, 18]. In the present study, a correct diagnosis of NETAoVs without symptoms was confirmed preoperatively in 4 patients for a preoperative diagnostic accuracy of 100%; the excellent results reflected the use of EUS-guided biopsy.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…For definite diagnosis, immunohistochemical staining is needed after tumor biopsy. Because of the finding of a submucosal tumor at the ampulla on endoscopy, the rate of preoperative histological diagnosis on endoscopic biopsy is low, ranging from 14 to 66% [2, 5, 13, 18]. In the present study, a correct diagnosis of NETAoVs without symptoms was confirmed preoperatively in 4 patients for a preoperative diagnostic accuracy of 100%; the excellent results reflected the use of EUS-guided biopsy.…”
Section: Discussionmentioning
confidence: 47%
“…The small bowel is most common site of neuroendocrine tumor occur, however, neuroendocrine tumor very rarely occurs at the ampulla of Vater [13]. Neuroendocrine tumors originating in the duodenum represent merely 4% of all carcinoid tumors [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two months after last observation, the major papilla was further swollen a and central depression was remarkable in the duodenoscopic view (a). However, the orifice was not recognized and needle-knife incision was performed to obtain biopsy (b) While 90% of 5-year survival has been achieved by local excision of the ampulla [3,9], recent papers have emphasized the necessity of aggressive surgical resection for the possible cure for ampullary carcinoid [10,11]. Of course, considering the several complications of pancreatoduodenectomy, conservative treatment or endoscopic papillotomy should be taken into consideration in patients with a very high age or associated co-morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Since tumor size has not been clearly established to correlate with lymph nodal positivity status, pancreaticoduodenectomy is often recommended as the treatment of choice for tumors of any size with no distant spread [9] [12] [13]. However, less invasive procedures like local excision and endoscopic resections have also been successfully attempted, especially for ANET less than 2 cm size or in high risk surgical candidates [4] [5] [14]. Extensive debulking surgery should be considered in patients with hormonal hypersecretion, even in the presence of advanced disease (extensive local or distant metastasis) since it has been shown to offer survival rates of up to 80% at 5 years [7].…”
Section: Therapeutic Optionsmentioning
confidence: 99%